Exploring Teacher Resilience in Indonesia: A Scoping Review of Challenges, Strategies, and Support Mechanisms - Mukadimah, Hertati (Jurnal Ilmiah WUNY, 2025)
The number of students enrolled in Indonesia's education departments has remained high, as seen in the case of the English Education Program at Universitas Negeri Yogyakarta (UNY) and there are over 3.4 million active teachers nationwide. However, teachers face various challenges, including heavy workloads, low salaries, inadequate facilities, and the pressures of adapting to rapid curriculum changes and the Covid-19 pandemic. This study explores factors contributing to the resilience of Indonesian teachers by elaborating it to the paradigm from Beltman (2020); person-focused perspective, process-focused perspective, context-focused perspective, and system-focused perspective. The study is intended to capture broad aspects of resilience, such as psychological, social, professional, and social factors that support teachers in overcoming challenges.  This article adopts a scoping review methodology, following Arksey and O'Malley's (2005) framework, to map existing literature on teachers' resilience in Indonesia over the last five years. The review process includes five stages: identifying the research question, selecting relevant studies, study selection, charting the data, and summarizing the results. The findings emphasize that teacher resilience in Indonesia is not solely an individual trait but rather a dynamic interplay of personal characteristics, professional skills, social support, and organizational factors. The research highlights the crucial role of self-efficacy, emotional regulation, and social networks, as well as the importance of school leadership and community support in fostering resilience.